Kepemimpinan Kyai dalam Pondok Pesantren Modern - Isa Anshory; Gali Nurma Saudi; Sabila Nurul Azizah; Salma Navi’ati Kholisa Dewi (STIKes Ibnu Sina Ajibarang, 2024)
This research is a literature study which aims to examine the form of kyai leadership in modern Islamic boarding schools. This research data was taken from research results related to kyai leadership and modern Islamic boarding schools published in scientific journals and various reference books that are relevant to this research. The data in this research was collected through documentation techniques, then analyzed inductively. The research results show that Kyai choose a democratic leadership pattern in leading modern Islamic boarding schools. This is caused by several factors related to the effectiveness of Islamic boarding school development and leadership style.